USE OF ROLE-PLAYING GAMES IN EDUCATION - Xurramov Azizbek Abdivali o’g’li; Laylo Alimjonova (Journal of new century innovations, 2022)
Research suggests that game-based education encourages motivation and drives academic progress. Role-playing games integrate challenge, narrative, and collaboration within the overarching theme of character and player development. The review article delves into literature around the international use of role-playing games in education. The findings from multiple qualitative and quantitative research studies are analysed to identify trends and gaps in the research. The findings support the suggestion that role-playing games are being used to develop collaboration and communication skills, and that their educational potential increases when paired with a formal debrief period. Limitations to the current use of role-playing games are identified as varied levels of student and teacher experience with games and small sample sizes of existing studies.